Chemical Bonding as a New Avenue for Controlling Excited‐State Properties and Excitation Energy‐Transfer Processes in Zinc Phthalocyanine–Fullerene Dyads. Issue 12 (28th January 2021) - Li, Zi‐Wen; Yang, Jia‐Jia; Liu, Xiang‐Yang; Fang, Wei‐Hai; Wang, Haobin; Cui, Ganglong
Abstract: Whether chemical bonding can regulate the excited‐state and optoelectronic properties of donor–acceptor dyads has been largely elusive. In this work, we used electronic structure and nonadiabatic dynamics methods to explore the excited‐state properties of covalently bonded zinc phthalocyanine (ZnPc)‐fullerene (C60 ) dyads with a 6–6 (or 5–6) bonding configuration in which ZnPc is bonded to two carbon atoms shared by the two hexagonal rings (or a pentagonal and a hexagonal ring) in C60 . In both cases, the locally excited (LE) states on ZnPc are spectroscopically bright. However, their different chemical bonding differentiates the electronic interactions between ZnPc and C60 . In the 5–6 bonding configuration, the LE states on ZnPc are much higher in energy than the LE states on C60 . Thus, the excitation energy transfer from ZnPc to C60 is thermodynamically favorable. On the other hand, in the 6–6 bonding configuration, such a process is inhibited because the LE states on ZnPc are the lowest ones. More detailed mechanisms are elucidated from nonadiabatic dynamics simulations. In the 6–6 bonding configuration, no excitation energy transfer was observed. In contrast, in the 5–6 bonding configuration, several LE and charge‐transfer (CT) excitons were shown to participate in the energy‐transfer process. Further analysis reveals that the photoinduced energy transfer is mediated by a CT exciton, such that electron‐ and hole‐transfer processes take place in a concerted but asynchronous manner in the excitation energy transfer. It is also found that high‐level electronic structure methods including exciton effects are indispensable to accurately describe photoinduced energy‐ and electron‐transfer processes. Furthermore, this work opens up new avenues for regulating the excited‐state properties of molecular donor–acceptor dyads by means of chemical bonding. Abstract : Two compounds, two natures : Electronic structure and nonadiabatic dynamics methods were used to explore the excited‐state properties of two zinc phthalocyanine (ZnPc)‐fullerene dyads. In one bonding configuration, excitation energy transfer from ZnPc to C60 is inhibited; in the other, this process is thermodynamically favorable, with locally excited and charge‐transfer excitons being shown to participate in the energy‐transfer process.